Effects of Supplementing Corn Silage to Fall-Calving Heifers and Cows Grazing Bermudagrass and Calf Performance and Physiology – Year 2 - Jaymelynn K. Farney; Tatiana M. Jones (Kansas Agricultural Experiment Station Research Reports, 2025)
The objective was to test the effect of supplemental feeding on cows grazing bermudagrass pastures on cow-calf performance and pasture management. In a completely randomized design, (n = 24) primiparous and multiparous Angus-based cross cows were allocated to bermudagrass pasture with one of two levels of supplemental feeding (nonsupplemented or supplemented at 1% of BW on a DM basis of corn silage). Each treatment consisted of (n = 4) pastures stocked with three cows of different ages, a young (first-calf heifer), middle-aged (3-5 yrs.), and old (≥ 6 yrs.) cow, each averaging 146 ± 3 d of gestation at turnout. Cows were fed silage (32-42% DM and 7.83% CP) daily in fence-line bunks, with feeding amount being adjusted at each weigh date. Cows were weighed on two consecutive days prior to turnout (middle of the second trimester), midpoint (beginning of the third trimester), and at about 2 weeks prior to the estimated calving date for the herd. Body weight, body condition score (BCS), hair score, hair length, and rump fat measurements were taken at each weigh date. Following the final measurement day, cows were relocated to calving pastures consisting of a mixture of bermudagrass, tall fescue, and prairie grass. Calves were weighed at birth and used in weigh-suckle-weigh to estimate milk output. Forage accumulation (FA) and forage mass (FM) were estimated every 28 days using the paired-cage method. Supplementation did not affect cow body weight, body condition score, hair score, or hair length during gestation (P > 0.13). During peak lactation, BCS (P > 0.35) and cow weights (P = 0.79) were not different. Calf birth weight was not affected by their dams being fed corn silage in late gestation (P = 0.91). Although visual BCS did not differ, cows that were supplemented with corn silage measured a greater rump fat accumulation than non-supplemented cows through the end of the second trimester (P = 0.06). Forage mass and forage accumulation did not differ (P > 0.78) based on supplementation method. Corn silage supplementation during late gestation, while cows graze growing bermudagrass, had no physiological effects on cows or calves. Contrary to a previous year, supplementation had no effect on available forage.
Keywords: BCS; substitution; growth; cow-calf